Percepção ambiental: como os corpos d’água e a biodiversidade aquática são percebidos por jovens de ensino fundamental em Rio Verde – Goiás - Oliveira, Rodolfo Pimentel (2017)
Humanity goes through an environmental crisis, the modernization of society caused deep changes in the behavior of the whole society, there was intensification of environmental impacts in a systemic way, not restricted to the cities. The severity of the damage has not yet been dimension, but certainly, puts endangered numerous species, particularly serious situation of Cerrado, a biodiversity hotspot that is in constantly impact of agricultural activities, especially aquatic organisms, which are little studied. To preserve the quality of the environment and the survival of biodiversity, there must be involvement of society, for this, individuals have to realize, since the youth, the factors that build the environment. For this reason, was investigated in Rio Verde - Goiás, one of the largest producers of grains in the country, the perceptions of elementary school students in a countryside school and a city school about aquatic biodiversity, through questionnaires with students, observations and interviews with teachers, managers and coordinators involved. It was questioned 140 students in sixth and ninth years of elementary school II and applied 8 interviews. The results are, the perception of aquatic biodiversity and water resources is quite shallow, poor. They do not realize the wealth of aquatic biodiversity and not dialogue about their importance to the ecosystem. They have difficulty to identify environmental impacts and suggest mitigation measures. There is no difference between the perception of the students of the countryside and the city, going contrary to the social movements fighting for the identity of the camp residents. Worrying finding is that countryside students have serious theoretical difficulties, failing to answer a number of questions. We conclude that there’s no difference between the students from the countryside and the city, being need to promote environmental education consistent inside the context of students and allow the development of the awareness of students to understand the aquatic biodiversity and how it relate to many human activities.